Navigating geopolitical and trade megatrends: Public export finance in a world of change - Andreas Klasen; Simone Krummaker; Julia Beck; James Pennington (Global Policy, 2024)
Ensuring exporters can access finance is critical for governments as they look to encourage trade and drive economic growth. However, firms face challenges in securing export finance and trade credit insurance as geopolitical and trade megatrends lead to increased political, market and credit risks. In a dynamic global landscape, the role of export credit agencies (ECAs) has never been more important. Based on the `Futures Triangle' analytical framework and drawing on qualitative data from 35 semi-structured interviews and expert discussions using thematic analysis, this research assesses the implications of key megatrends for ECAs. It presents new insights into the impact on strategies, products and operations: The evolution of mandates towards a `growth promoter' in a `whole-of-government' approach, the necessity to introduce new products and the need to balance multiple priorities such as export growth, support for small and medium-sized enterprises (SMEs), inclusive trade, climate action and impact on developing markets. The recommendations are intended to help policymakers and public finance practitioners understand and respond strategically to global changes.
Keywords: 320